Association of plasma microbial composition with a leaky gut in obesity-related osteoarthritis: An exploratory study. Issue 4 (December 2022) - Arbeeva, Liubov; Azcarate-Peril, M. Andrea; Cui, Yang; Nelson, Amanda E.; Loeser, Richard F.
Abstract: Objective: To examine the plasma microbiome for differences between obese individuals with and without osteoarthritis (OA) and its association with serum lipopolysaccharide (LPS). Design: Blood samples from 70 participants with body mass index (BMI) ​≥ ​30kg/m2 and age ≥55 years, with (cases) or without (controls) hand plus knee OA, were analyzed for serum LPS and composition of the plasma microbiome. The Dirichlet-multinominal recursive partitioning model (DM-RPart) was applied to microbiome compositional data to test the hypothesis that LPS levels distinguish plasma microbiome, accounting for BMI and age. Results: No significant differences in alpha diversity, or compositional differences between groups at the genus level, were seen between cases and controls (p ​= ​0.11). β-Diversity was significantly associated with serum LPS levels (p ​= ​0.01). DM-RPart resulted in an optimal tree with 3 divisions: 1) based on age (split at 69 years); 2) those older than 69 were split based on BMI; 3) those with BMI <39 ​kg/m2 were split based on LPS level (at 65 EU/ml). This resulted in 4 groups (nodes 2, and 5–7). Participants in node 2 were younger and the majority had no or mild OA. Those in nodes 5 and 6 were comparable in age and BMI but node 6 had higher LPS and more severe OA. Individuals in node 7 were older, had higher BMI, and the most severe OA. Conclusions: Our results suggest a relationship between serum LPS and the plasma microbiome in a subgroup of obese individuals with hand plus knee OA that could reflect differences in intestinal permeability.